To solve the equation 2(3x – 5) = 7x + 10, we’ll follow these steps:

- Distribute the 2 on the left side of the equation to both terms inside the parentheses:

2 * 3x – 2 * 5 = 7x + 10

This simplifies to:

6x – 10 = 7x + 10

- Now, let’s isolate the variable x by moving all the terms containing x to one side of the equation and the constants to the other side. We’ll do this by subtracting 6x from both sides of the equation:

6x – 6x – 10 = 7x – 6x + 10

This simplifies to:

-10 = x + 10

- Next, subtract 10 from both sides to isolate x:

-10 – 10 = x + 10 – 10

This simplifies to:

-20 = x

So, the solution to the equation 2(3x – 5) = 7x + 10 is:

x = -20